GATE, a General Architecture for Text Engineering. - Cunningham, Hamish (Computers & the Humanities, 2002)
This paper presents the design, implementation and evaluation of GATE, a General Architecture for Text Engineering. GATE lies at the intersection of human language computation and software engineering, and constitutes an infrastructural system supporting research and development of language processing software.